Complement activation in Hidradenitis suppurativa: Covert low-grade inflammation or innocent bystander? - van Straalen, K. R.; Dudink, K.; Aarts, P.; van der Zee, H. H.; van den Bosch, T. P. P.; Giang, J.; Prens, E. P.; Damman, J. (Frontiers in Immunology, 2022)
Hidradenitis suppurativa (HS) is a chronic auto-inflammatory skin disease with a complex and multifactorial pathogenesis involving both the innate and adaptive immune system. Despite limited evidence for local complement activation, conflicting results have been published on the role of systemic complement activation in HS. It was hypothesized that complement was consumed in highly inflamed HS skin, trapping complement from the circulation. Therefore, the aim of this study was to evaluate this local complement deposition in HS skin lesions using routine and commonly used complement antibodies. Direct immunofluorescence for C1q, C3c, C4d, C5b-9, and properdin was performed on frozen tissue sections of 19 HS patients and 6 controls. C5a receptor 1 (C5aR1) was visualized using immunohistochemistry. Overall, we found no significant local complement deposition in HS patients versus controls regarding C1q, C3c, C4d, C5b-9, or properdin on either vessels or immune cells. C5aR1 expression was exclusively found on immune cells, predominantly neutrophilic granulocytes, but not significantly different relatively to the total infiltrate in HS lesions compared with controls. In conclusion, despite not being able to confirm local complement depositions of C1q, C3c, C4d, or properdin using highly sensitive and widely accepted techniques, the increased presence of C5aR1 positive immune cells in HS suggests the importance of complement in the pathogenesis of HS and supports emerging therapies targeting this pathway.